Implementation of Financial Reports Based on Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) at the Henku Mere Store - Yuni Anggraini; Belinda Yunika; Kemas Welly Angga Permana; Putri Ambarwati (Journal of Education Technology Information Social Sciences and Health, 2024)
Financial reports for MSMESs are important information to achieve the success of a business. The purpose of this study is provide an overview and iinformation that can help MSME shop owners, namely the Accounting Standars for Micro, Small and Medium Enterprises (SAK EMKM). The research object is the Henku Mere shop which is engaged in tranding, namely buying goods and reselling them to consumers. This study uses a qualitative method. The type of data used by the author in this study is primary data inthe form of interviewa and secondary data in the form of sales transaction dokuments, purchases and a brief history of the Henku Mere store. Data collection technicques that the authors did in this study were interviews and direct observation. The results of the study show that Henku Mere store has not prepared and produced financial reports based on SAK EMKM. The entity uses only recorded notes so that information on sales of merchandise and purchasesof merhandise inventory, whererevenue minus expenses equals profit. As for the preparation of the financial statement and notes to the financial position, income statement and notes to the financial statements for the current period January to March 2023.